Citation Trend of Byline and Dateline Articles of “The Guardian” - Ravikumar, S.; Singh, Angom Jeevan (Journal of Information and Knowledge, 2020)
The objective of the paper is to examine the citation pattern of Byline and Dateline articles of “The Guardian” newspaper during 2001-2010. During the study period, there were 5480 records (newspaper articles) with 4101 citations to different scholarly publications indexed in Web of Science up to 31st December 2015.The highest citation of the Guardian newspaper was 1833 (44.70%) during the year 2010, followed by 1004 (24.48%) citations in the year 2009, and the lowest was 22 (0.54%) citations in the year 2001. The study found that there is a gradual increase in citing Byline newspaper articles from 2001 onwards in scholarly publications, except in the year 2004,whereas, there is a gradual increase in Dateline newspaper articles citations from 2001 onwards. The study also found that the citations do not depend on the readership of the newspaper and there is significant difference in citing the byline and dateline articles in the scholarly publications during 2001-2010.